LEVEL OF ADDITION OF TILAPIA MEAL TO DRIED NOODLES - M. Fauzie Ahmadi; Junianto Junianto; Asep Agus Handaka Suryana; Rusky Intan Pratama (Universitas Mataram, 2024)
Increasing the protein content of dry noodles can be done by adding tilapia fish meal. This research aims to determine the maximum percentage level of adding tilapia meat flour in the manufacture of dry noodle products that is still preferred by panelists. The research was conducted from February to April 2024 at the Fishery Product Processing Laboratory, Faculty of Fisheries and Marine Sciences, Padjadjaran University. This research method was experimental with 4 treatments with levels of tilapia fish meal addition of 0%, 7.5%, 10% and 12.5%. The parameters observed were the level of preference for color, aroma, texture and taste of dried noodle products using a hedonic test. The research results concluded that the addition of 10% tilapia fish meat flour was the maximum addition treatment that was still preferred based on the hedonic test with an average value of color 7.24, aroma 6.76, texture 6.92, and taste 6.6 with an overall average is 6.88 which is close to 7 which can be defined as liking. And has a protein content of 17.88%, water content of 12.78%, ash content of 2.01%, fat content of 0.49%, and carbohydrate content of 66.84%.